Highly Porous Yet Transparent Mechanically Flexible Aerogels Realizing Solar-Thermal Regulatory Cooling - Lian, Meng; Ding, Wei; Liu, Song; Wang, Yufeng; Zhu, Tianyi; Miao, Yue‑E.; Zhang, Chao; Liu, Tianxi (Nano-Micro Letters, 2024)
The demand for highly porous yet transparent aerogels with mechanical flexibility and solar-thermal dual-regulation for energy-saving windows is significant but challenging. Herein, a delaminated aerogel film (DAF) is fabricated through filtration-induced delaminated gelation and ambient drying. The delaminated gelation process involves the assembly of fluorinated cellulose nanofiber (FCNF) at the solid–liquid interface between the filter and the filtrate during filtration, resulting in the formation of lamellar FCNF hydrogels with strong intra-plane and weak interlayer hydrogen bonding. By exchanging the solvents from water to hexane, the hydrogen bonding in the FCNF hydrogel is further enhanced, enabling the formation of the DAF with intra-layer mesopores upon ambient drying. The resulting aerogel film is lightweight and ultra-flexible, which possesses desirable properties of high visible-light transmittance (91.0%), low thermal conductivity (33 mW m−1 K−1), and high atmospheric-window emissivity (90.1%). Furthermore, the DAF exhibits reduced surface energy and exceptional hydrophobicity due to the presence of fluorine-containing groups, enhancing its durability and UV resistance. Consequently, the DAF has demonstrated its potential as solar-thermal regulatory cooling window materials capable of simultaneously providing indoor lighting, thermal insulation, and daytime radiative cooling under direct sunlight. Significantly, the enclosed space protected by the DAF exhibits a temperature reduction of 2.6 °C compared to that shielded by conventional architectural glass. Highlights: 1 A lamellar-structured fluorinated cellulose nanofiber aerogel film is prepared by filtration-induced delaminated gelation and ambient drying. 2 The aerogel film demonstrates exceptional mechanical flexibility and resistance to complex deformations. 3 The aerogel film displays low thermal conductivity, high visible-light transmittance and superior selective infrared emissivity, rendering it high solar-thermal regulatory cooling performance.